1999
DOI: 10.1016/s0378-1119(99)00160-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the components of the putative mammalian sister chromatid cohesion complex

Abstract: Establishing and maintaining proper sister chromatid cohesion throughout the cell cycle are essential for maintaining genome integrity. To understand how sister chromatid cohesion occurs in mammals, we have cloned and characterized mouse orthologs of proteins known to be involved in sister chromatid cohesion in other organisms. The cDNAs for the mouse orthologs of SMC1 S.c. and SMC3 S.c. , mSMCB and mSMCD respectively, were cloned and the corresponding transcripts and proteins were characterized. mSMCB and mSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 19 publications
(39 reference statements)
7
79
0
Order By: Relevance
“…Among these, two are particularly striking. First, there are several reports that G 1 ͞S progression is regulated, positively or negatively, by chromosomal proteins that originally were identified by their roles in meiotic or mitotic sister chromatid cohesion or meiotic interhomolog interactions, none of which can take place in mitotic G 1 cells (48)(49)(50)(51)(52)(53)(54). The human homologs of these proteins, the chromosome morphogenesis protein Spo76͞BIMD͞AS3 and the securin Pds1͞Cut2, are both implicated as tumor suppressor proteins, and modulation of progression through G 1 by these proteins can be directly linked to cancer (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, two are particularly striking. First, there are several reports that G 1 ͞S progression is regulated, positively or negatively, by chromosomal proteins that originally were identified by their roles in meiotic or mitotic sister chromatid cohesion or meiotic interhomolog interactions, none of which can take place in mitotic G 1 cells (48)(49)(50)(51)(52)(53)(54). The human homologs of these proteins, the chromosome morphogenesis protein Spo76͞BIMD͞AS3 and the securin Pds1͞Cut2, are both implicated as tumor suppressor proteins, and modulation of progression through G 1 by these proteins can be directly linked to cancer (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported previously (21) that the bulk of SMC3 undergoes redistribution from the chromosome vicinity to the cytoplasm during prometaphase and back to the chromatin in telophase. Therefore the vast majority of SMC3, along with SMC1, is localized within the cytoplasm during the cell cycle.…”
Section: ␤-Catenin/tcf4 Transactivates the Cohesin Smc3 Promotermentioning
confidence: 92%
“…For example, the homozygous deletion in HCT116 colon carcinoma cells of the hSecurin gene leads to retardation of sister chromatid separation and a high rate of chromosomal loss because of defective Scc1 cleavage (24). On the other hand, overexpression of the murine orthologue of Scc1 (PW29 protein) in mouse fibroblast leads to inhibition of proliferation, implicating this protein and its complex with SMC proteins in the control of mitotic cell cycle progression (21). We have shown previously (26) that overexpression of Smc3 in 3T3 fibroblasts causes cell transformation and enhances cell proliferation.…”
Section: ␤-Catenin/tcf4 Transactivates the Cohesin Smc3 Promotermentioning
confidence: 99%
“…The recruitment of the cohesin complex components occurs prior to the start of replication, namely, during G1 phase in yeast [68] and telophase in higher eukaryotes [6972], and coincides with the loading of pre-replication complex onto the chromosome, which indicates that ORC could play a role in cohesin recruitment to the chromatin. Several studies in the yeast Schizosaccharomyces pombe , confirmed that the ORC5 interacts with cohesin complex components and is necessary for its recruitment to centromeric regions of chromosomes [73].…”
Section: Sister Chromatid Cohesionmentioning
confidence: 99%